Machiavelli the art of teaching people what to fear - Boucheron, Patrick (New York Other Press, 2020)
In a series of poignant vignettes, a preeminent historian makes a compelling case for Machiavelli as an unjustly maligned figure with valuable political insights that resonate as strongly today as they did in his time. Whenever a tempestuous period in history begins, Machiavelli is summoned, because he is known as one for philosophizing in dark times. In fact, since his death in 1527, we have never ceased to read him to pull ourselves out of torpors. But what do we really know about this man apart from the term invented by his detractors to refer to that political evil, Machiavellianism? It was Machiavelli's luck to be disappointed by every statesman he encountered throughout his life--that was why he had to write The Prince. If the book endeavors to dissociate political action from common morality, the question still remains today, not why, but for whom Machiavelli wrote. For princes, or for those who want to resist them? Is the art of governing to take power or to keep it? And what is "the people?" Can they govern themselves? Beyond cynical advice for the powerful, Machiavelli meditates profoundly on the idea of popular sovereignty, because the people know best who oppresses them. With verve and a delightful erudition, Patrick Boucheron sheds light on the life and works of this unclassifiable visionary, illustrating how we can continue to use him as a guide in times of crisis"
Includes bibliographical references.
Keywords: Machiavelli, Niccolò, 1469-1527.